Development of STEM-Based Biology E-Module to Improve Student Learning Outcomes - Irdawati Irdawati; Moralita Chatri; Kurnia Wulansari; Abdul Razak; Suci Fajrina (Jurnal Penelitian Pendidikan IPA, 2023)
One of the factors for improving the quality of education in schools is teaching materials. Based on the results of observations at SMAN 1 Sitiung students have not used e-modules but use electronic teaching materials in the form of pdf files downloaded from the internet and only in the form of writing and a few pictures. Based on the questionnaire results, it is known that students have difficulty understanding the concept of the respiratory system material. This causes low student learning outcomes as evidenced by the daily test scores that are still below the minimum completeness criteria. So, it takes teaching materials that can help in visualizing the subject matter. This type of research is Plomp model development research which consists of three stages: the initial investigation stage, the development or prototyping stage, and the assessment stage. The research subjects were class XI students at SMAN 1 Sitiung for the 2022-2023 academic year. Validation results by the validator on e-module-based Science Technology Engineering and Mathematics (STEM) show an average grade 88.05% (very valid). Practical results by Biology teachers showed an average score of 87.50% (very practical) and 88.28% students (very practical). Effectiveness test data has effectiveness with very effective criteria in terms of cognitive competency assessment with an average of 83.59, affective with an average of 84.24, and psychomotor with an average of 81.08